STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA SMA NEGERI 1 TUREN MALANG - Moch Choiron Ardiyansyah; Dian Mohammad Hakim; Moh Eko Nasrullah (VICRATINA, 2022)
Character education is very important to improve the personal and community environment. Islamic Religious Education Teachers (PAI) have the mandate to teach and educate their students with religious knowledge, they have the noble character for life in the future.  During a moral crisis that hit the country.  SMA Negeri 1 Turen Malang is here as a forum to educate a moral generation.  This research uses a field research method with the type of case study research.  In collecting data, the researcher used the method of observation, documentation, and interviews.  The data obtained are data from observations, interviews, and documentation which are reduced or processed to obtain valid conclusions.  The results showed that.  1) PAI teacher planning in character building at SMA Negeri 1 Turen, namely through the cultivation of character values instilled by PAI teachers, namely Religious Values, Honesty, Discipline, Responsibility, Care, Curiosity, Confidence, Love of Cleanliness and Neatness, and  Tolerance.2).  The implementation of PAI teachers in the formation of student character by means;  First, by example.  Second, is the cultivation of discipline.  Third, by habituation.  3).  Evaluation, Evaluation is divided into two types, first, direct evaluation, which is an evaluation that is carried out on the spot, and indirect evaluation so that new rules are issued.